Prevalence, awareness, treatment and control of arterial hypertension depending on regional characteristics in Russia: results of the ESSE-RF study 2012-2022 — evidence of COVID-19 impact? - S. A. Maksimov; S. A. Shalnova; Yu. A. Balanova; A. E. Imaeva; V. A. Kutsenko; M. B. Kotova; G. A. Muromtseva; S. E. Evstifeeva; A. V. Kapustina; N. S. Karamnova; O. B. Shvabskaya; T. V. Repkina; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To analyze the individual association of arterial hypertension (AH) prevalence, awareness, treatment, and control with regional characteristics within the national epidemiological ESSE-RF study (2012-2022), assessing the impact of the COronaVIrus Disease 2019 (COVID-19) pandemic.Material and methods. The analysis used pooled data from the ESSE-RF study across three time periods: ESSE-RF-1 (2012-2014), ESSE-RF-2 (2017-2018), ESSERF-3 (2020-2022). The final analytical sample across all three periods 55.725 men and women aged 25-74 years. The presence, awareness, treatment and of AH were considered as individual outcomes. Regional living conditions were assessed using the "Economic", "Demographic", "Industrial" and "Social" indices based on data from the National Medical Research Center for Therapy and Preventive Medicine. Statistical analysis was performed using generalized estimating equations (logistic regression models) with calculation of Odds Ratios and 95% Confidence Intervals. To assess the impact of the COVID-19 pandemic on the associations between regional living conditions and AH prevalence, awareness, treatment, and control, separate analyses were performed in the ESSE-RF-1 2012-2014 and ESSERF-3 2020-2022 samples.Results. Improvement of social living conditions was associated with a decreased probability of AH (0.90; 0.85-0.95), increased AH treatment (1.13; 1.02-1.25), and control (1.11; 1.01-1.22). A demographic shift toward a younger age structure in regions was associated with a decreased AH probability (0.83; 0.76-0.91). Increasing industrial development in regions was associated with decreased AH treatment (0.87; 0.80-0.96). Compared to sex, age, and obesity, regional indices contributed significantly less to the studied outcomes. Nevertheless, the contribution of regional living conditions was comparable to such individual predictors as education level, income, and urban/rural residence. Substantial differences were observed in the associations between regional indices and AH treatment/control in the pre-pandemic (presence of multiple associations) and pandemic (associations virtually absent) study periods.Conclusion. The results of the study indicate associations of AH prevalence, treatment, and control with regional living conditions. The attenuation or even inversion of associations between regional characteristics and AH treatment/control during the COVID-19 period confirms the significance of the pandemic as a powerful driver of changes in individual and population health-related behavior.